1985
DOI: 10.1148/radiology.157.2.3901105
|View full text |Cite
|
Sign up to set email alerts
|

Spontaneous resolution of cholelithiasis in infants.

Abstract: Follow-up sonographic studies of five infants whose initial sonograms had displayed evidence for the diagnosis of cholelithiasis demonstrated spontaneous resolution of the gallbladder defects. These defects may have been caused by tumefactive sludge with acoustic shadowing. Whether sludge or gallstones are being imaged, in the absence of other clinical or imaging evidence of biliary tract disease, conservative (i.e., nonsurgical) management and serial sonograms are recommended.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
22
0
3

Year Published

1986
1986
2004
2004

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(25 citation statements)
references
References 0 publications
0
22
0
3
Order By: Relevance
“…They also assert that surgical treatment is unnecessary even with definitive existence of the CBD obstruction because spontaneous elimination of gallbladder calculi can be promoted with percutaneous cholangiography, bile duct irrigation, and biliary drainage. On the basis of the technical difficulties and the high possibility of surgical complications such as cholecystostomy, bile peritonitis, or biliary stricture [3], Keller et al [4] have suggested conservative treatment for neonates and young infants using PTC.…”
Section: Discussionmentioning
confidence: 99%
“…They also assert that surgical treatment is unnecessary even with definitive existence of the CBD obstruction because spontaneous elimination of gallbladder calculi can be promoted with percutaneous cholangiography, bile duct irrigation, and biliary drainage. On the basis of the technical difficulties and the high possibility of surgical complications such as cholecystostomy, bile peritonitis, or biliary stricture [3], Keller et al [4] have suggested conservative treatment for neonates and young infants using PTC.…”
Section: Discussionmentioning
confidence: 99%
“…Nos últimos cinco anos, a incidência de colelitíase no período neonatal tem aumentado em razão do aumento do uso do ultra-som abdominal nesta faixa etária 4,5,8 . Geralmente, o diagnóstico é acidental, durante a investigação de outras patologias ou em exames de rotina em unidades de terapia intensiva neonatal [8][9][10] .…”
Section: Discussionunclassified
“…Entretanto, no período neonatal, os seguintes fatores de risco têm sido relacionados: prematuturidade, sepsis, nutrição parenteral total, uso prolongado de Furosemida, hemólise e mal-formações de vias biliares 1,4,7,8 . A colelitíase neonatal pode caracterizarse pelo seu diagnóstico acidental e possível resolução espontânea [8][9][10][11] . Este trabalho tem como objetivo relatar um caso de colelitíase assintomática em um lactente jovem, com evolução espontânea, seguido de uma revisão de literatura.…”
Section: Introductionunclassified
“…It is probably related to abnormal content of the GB and cholethiasis reported in newborn and infancy with the following causative factors: prematurity, infection, dehydration, parenteral nutrition, furosemide, gastrointestinal dysfunction [6][7].…”
Section: Discussionmentioning
confidence: 99%
“…This entity is thus probably due to a transient bile disturbance resulting from deficient glucurono-conjugation [2,6]. As disappearance of cholelithiasis has been reported [6,7], it may be sug- gested that in some cases of mild obstruction, spontaneous resolution could occur without a percutaneous cholangiogram. However it has to be pointed out that cholangitis was present in 4 of our cases Fig.3.…”
Section: Discussionmentioning
confidence: 99%